PERLINDUNGAN HUKUM TERHADAP HAK KEBEBASAN BERPENDAPAT BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DENGAN PERSPEKTIF HAK ASASI MANUSIA - Puput Pandu Ariyo Seno (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Legal research is aimed to know about the protection of freedom of speech through the medium of the internet which is regulated in the law number 11 year 2008 aboutinformation and transaction of electronic reviewed from the perspective of human rights. This research is a normative law research that is prescriptive. The method used in this research is juridical normative.  Secondary data sources used include the primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques used are literature studies and cyber media. The data obtained were then analyzed with the interpretation of grammatical and interpretion of the systematic of the provisions contained in the law of information and electronic transactions. The result showed that in the law  number 11 year 2008 abaout information and electronic transactions can already be said to have been protection the freedom of expression that is owned by someone as a personal right to communicate through the medium of the internet. But there are some things in law enforcement as if violating human rights. As has been outlined that provisions in the law of informasion and electronic transaction related to freeom of speech is only regulated in one article and there is only a prohibition without the accompanied rights.Based on that, then that provision still raised multiple interpretations and obscurity. So it requires more settings in the law of information and electronic transactions. As a human rights are also included in the political someone and and the personal, freedom expressed absolute opinion should be protected and can not be reduced. But remember that in the right also cause an obligation to respect and appreciate the rights of others, then the implementation of yhe on the right can be limited through the legislation. While in the legislation and transaction information elekronic there is no restrictions clear about it.